Analysis of Privacy Preserving methods in 4G and 5G Cellular Networks (International Journal of Food and Nutritional Sciences, 2022)
This paper intends to present a survey of privacy preserving methods that are available to provide data security in 4G and 5G mobile networks. A brief classification of threat models such as attacks on privacy, availability, privacy, and integrity has been provided. Then, based on the various categories of authentication and privacy saving methods the techniques are classified in categories like- handover authentication, deniable authentication, key agreement, three factor authentication, RFID authentication.